Sex and disability - McRuer, Robert, 1966-; Mollow, Anna, 1970- (Duke University Press, 2012)
This collection brings together scholars and artists in disability studies, sexuality, queer theory, and feminism, to show how much sexuality studies and disability studies have to learn from each other.